Pre-Marital Test of Genetic Compatibility for Effective Child Health: An Islamic Perspective - Kamal-deen Sulaiman (AlQalam Journal of Medical and Applied Sciences, 2018)
Debates on pre-marital genotype compatibility test for effective child health has received much attention in recent times among medical practitioners, biological scientists and Islamic Scholars. However, some marriage counselors, religious leaders, followers and even prospective spouses have questioned such medical recommendation as unnecessary due to its limitation of the natural laws of love and religion. Some claim, with legitimate authority that it contradicts the Islamic etiquettes of spouse selection and marriage approval. This study therefore, intends to examine the argument against pre-marital test of genetic compatibility with the views of its protagonists. The study revealed that, Islamic teachings offer a great deal in the prevention and control of genetic diseases to Islamic community. In Islam any measure or step that is taken to safe guard the health and to give it an immunity against any negative force external or internal as long as that measure is not contrary to the teaching of Shari’ah is lawful consider the following.It is recommended tha, Pre-marital examination should be encouraged which may detect the trait in those intending to get married. And that governments and Islamic institutions spread understanding of the importance of pre-marital genetic tests and encourage their use. The paper concluded that, healthy living is part and parcel of Islam, introduced with the inception of Islam more than 14 centuries ago.